Acetic acid triggers cytochrome c release in yeast heterologously expressing human Bax - Guedes, Joana P. (2022)
Proteins of the Bcl-2 protein family, including pro-apoptotic Bax and anti-apoptotic Bcl-xL, are critical for mitochondrial-mediated apoptosis regulation. Since yeast lacks obvious orthologs of Bcl-2 family members, heterologous expression of these proteins has been used to investigate their molecular and functional aspects. Active Bax is involved in the formation of mitochondrial outer membrane pores, through which cytochrome c (cyt c) is released, triggering a cascade of downstream apoptotic events. However, when in its inactive form, Bax is largely cytosolic or weakly bound to mitochondria. Given the central role of Bax in apoptosis, studies aiming to understand its regulation are of paramount importance towards its exploitation as a therapeutic target. So far, studies taking advantage of heterologous expression of human Bax in yeast to unveil regulation of Bax activation have relied on the use of artificial mutated or mitochondrial tagged Bax for its activation, rather than the wild type Bax (Bax ). Here, we found that cell death could be triggered in yeast cells heterologoulsy expressing Bax with concentrations of acetic acid that are not lethal to wild type cells. This was associated with Bax mitochondrial translocation and cyt c release, closely resembling the natural Bax function in the cellular context. This regulated cell death process was reverted by co-expression with Bcl-xL, but not with Bcl-xLC, and in the absence of Rim11p, the yeast ortholog of mammalian GSK3. This novel system mimics human Bax regulation by GSK3 and can therefore be used as a platform to uncover novel Bax regulators and explore its therapeutic modulation.